Composites in extreme environments: effects of high strain rate, humidity and temperature - Quino, G; Pellegrino, A; Petrinic, N (IOP Science, 2021)
Multifunctionality, lightweight and resistance to corrosion are some of the several advantages that fibre composites display with respect to other materials across a wide range of applications. In aerospace and marine industry, however, we can encounter challenges arising from certain working conditions that can significantly affect the mechanical response and integrity of composite structures. First, humidity or water exposure can induce reduction of the material strength and stiffness. Second, hot or cold temperatures that change the level of ductility in the composite. Finally, dynamics loads that may appear during service require strain rate sensitive properties to be considered. In this work, we show experimental capabilities and methodologies developed to account for all those three effects: rapidly applied loads (impact), humidity and temperatures from -55°C to 93°C. This understanding sets the basis for the development of advanced models to design better structures.